In-House Virtual Surgical Planning Using 3D Slicer: Outcomes of Free Fibular Flap Mandibular Reconstruction - Redo Alif Iszar; Mulyadi; Ozi Rahmat Firdaus (HM Publisher, 2026)
Background: Mandibular reconstruction following tumor resection remains a significant surgical challenge requiring precise restoration of facial symmetry and function. Virtual surgical planning has emerged as a transformative approach, yet its adoption remains limited by the high costs of commercial platforms and proprietary cutting guides. Methods: This proof-of-concept case series evaluated the operative outcomes and cost-effectiveness of an in-house virtual surgical planning workflow using 3D Slicer, a free open-source software platform, for mandibular reconstruction with free fibular flap without fibular cutting guides. Results: Four consecutive patients (three males, one female; mean age 39.0 years; standard deviation 13.1; range 28-58) who underwent mandibular reconstruction between July and December 2024 were included. Three patients presented with ameloblastoma and one with squamous cell carcinoma. Preoperative computed tomography data were processed using 3D Slicer version 5.6.2 to generate three-dimensional mandibular models through thresholding segmentation, followed by mirroring technique reconstruction and polylactic acid three-dimensional printing. The mean ischemic time was 51.0 minutes (standard deviation 10.7; 95% confidence interval 34.0-68.0), representing a 70.4% reduction compared with conventional approaches in published literature. The mean total operative time was 455.0 minutes (standard deviation 136.5; 95% confidence interval 237.8-672.2). Model printing costs of IDR 50,000-100,000 (approximately USD 3-7) represented a 99% reduction compared with commercial cutting guides. Conclusion: All flaps survived without complications. These preliminary findings suggest that simplified in-house virtual surgical planning using free open-source software provides a potentially cost-effective and efficient alternative for mandibular reconstruction, warranting validation in larger prospective studies.